TINJAUAN PERENCANAAN MANAJEMEN PADA GEDUNG ASRAMA KESATUAN BRIGADE MOBIL DI KABUPATEN KUBU RAYA - Nopriansyah, Nopriansyah Nopriansyah (RETENSI, 2021)
In line with the increasingly rapid development and population growth which is increasing in Kubu Raya Regency, the need for facilities and infrastructure for the city government includes housing for Brimob personnel in accordance with the regional budget. So the Mobile Brigade Unit Dormitory Building was built in Kubu Regency. The method for completing this final project uses literature studies that use data, namely, secondary and primary data. After that, based on the processed data, including field layout drawings, documentation, field observation results. Project costs include, Calculating Volume, Determining Unit Price Analysis, Calculating (RAB). SMK3 includes, Planning work items, Classification and Control of Accident Risk, Determining the Appropriate PPE and GER. Time covers Job Weight, Dependency Table, Time Schedule (Barchart and NWP), making S Curve. Human Resources include: Calculating labor requirements, making labor requirements and job duration. The final result of the Project Quality Management is a Quality Checklist Table or Specifications for the Construction of the Car Brigade Unit Dormitory Building in Kubu Raya Regency. The results of the analysis of the Budget Plan (RAB) for the construction of this dormitory building are: Rp. 14,061,856,628.70 (Fourteen Billion Sixty One Million Eight Hundred Fifty Six Thousand Six Hundred Twenty Eight Comma Seventy Rupiah), as well as the calculation results of time requirements or the duration of development using the Network Planning (NWP) method, namely the NWP method get a work duration of 336 days, while using the Barchard method get a job duration of 14 months. The SMK3 in the Construction of the Dormitory Building is Personal Protective Equipment (PPE) consisting of 120 head protectors, 110 gloves, 110 protective glasses, 110 boots, 110 full body harnesses, 370 masks of safety shoes 10 pairs and 120 pieces of Vest. As for (APK) consists of. Signs 5 pieces, Line Volleyball 20 pieces, and Scapolding 50 sets. The final result of the Project Quality Management is the Quality / Specification Checklist Table for the Construction of the Dormitory Building for the Mobile Brigade Unit in Kubu Raya Regency and the Mutual Check 0% (MC 0%) whether it is appropriate or not